PERBAIKAN TANAH LANAU UNTUK BAHAN JALAN MENGGUNAKAN LIMBAH BATA - Endaryanta, - (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT The earthquake in Bantul, Yogyakarta at Mei 27, 2006 appeared a lot of problems for peoples. Besides psychological and physical excesses,, a great deal of the rubbish material accumulated as the result of building destruction. This paper tries to implement the brick rubbish material for improving the soil street strength at villages. This experiment research that was done by CBR-test at pure soil as well as at soil with grain brick mixture is aimed to explain the appropriate grain brick composition must be mixed into soil in order to get a maximum strength of soil. The results of the research are: 1. adding grain brick into soil could increase the strength of soil bearing parallel with increasing the CBR-value.2. the fine grain brick significantly increase the strength of soil mix. 3. the CBR-value of soil mixed with grain brick is reached at 36%. Keywords : brick, rubbish, CBR, soil bearing, soil strength.